(untitled) (Acta Medica Academica, 2021)
Objective. This study aimed to describe Salmonella epidemiology and antimicrobial resistance in Greek children over the period of 2011-2017. Materials and Methods. A 7-year retrospective study (2011-2017) was performed, based on data recorded by the National Reference Centre for Salmonella, among children aged ≤14 years. Epidemiological data, serovar distribution and antimicrobial resistance patterns were recorded. Results. Overall, 2347 Salmonella isolates were collected (27 typhoid-paratyphoid). Salmonellosis cases increased by almost 2-fold in 2017 compared to 2011. The highest rates were reported in August, with infants being the most vulnerable group (17.9%). The majority of isolates were identified in stool samples (91%). Boys slightly outnumbered girls ( 1.05:1). Salmonella Enteritidis was the most prevalent serovar (28.5%), followed by Salmonella Typhimurium (12.2%) and Salmonella monophasic Typhimurium (10.4%). Non-typhoid isolates displayed low resistance rates to 3rd generation cephalosporins (1%) and ciprofloxacin (0.3%), while the corresponding resistance of typhoid isolates was 10% and 5% respectively. An increasing trend of Salmonella monophasic Typhimurium was recorded, associated with high rates of multidrug resistance, reaching a percentage of 97.8% in 2017. Conclusions. Salmonellosis epidemiology in Greek children is comparable to previously published European data. Antimicrobial resistance rates to 3rd-generation cephalosporins and ciprofloxacin for non-typhoid and typhoid-paratyphoid remain low. Notably, there is an increasing prevalence of Salmonella monophasic Typhimurium isolates, associated with multiple antimicrobial resistance.